EXPLORING BEHAVIORAL AND ATTITUDINAL BRAND LOYALTY USING TRIPARTITE MODEL OF ATTITUDE (Journal of Economics and Sustainability, 2020)
Previously, scholars have studied behavioral and attitudinal brand loyalties separately by. Brand loyalty was first studied with behavior as one dimension in the brand loyalty structure, which predominantly measures brand loyalty by repeat purchase. However, the stochastic paradigm that views behavior as a single dimension cannot explain the motivation for consistent repeat purchase behavior. Subsequently, the stochastic paradigm was replaced with a deterministic paradigm that views attitude as a single dimension of brand loyalty. Since brand loyalty is a psychological abstraction in nature, scholars viewed that a combined approach of behavior and attitude is more appropriate to address the issue of brand loyalty. This paper proposes a Tripartite Model of Attitude to explain the dimensions and determinants of brand loyalty by combining behavioral loyalty and attitudinal loyalty in one framework.Received 14 May 19. Revised 20 Jul 19. Accepted 2 Aug 19.